Renewing the centre evangelical theology in a post-theological era - Grenz, Stanley J. 1950-2005 (Grand Rapids, MI Baker Academic, 2000)
Includes bibliographical references and indexes.
Keywords: Theology, doctrinal -- history -- 20th century; Evangelicalism